Optimizing Interactive Learning Management System (LMS) in Improving Students' English Language Skills - Nisak, Sayida Khoiratun (CV. Zabags Qu Publish, 2024)
This study aims to evaluate the effectiveness of the platform in improving the quality of learning for students at the Al-Mujaddid Sabak Islamic Institute. This study seeks to understand how interactive features such as discussion forums, automatic quizzes, online assignments, and virtual classes can contribute to improving student engagement, motivation, and learning outcomes. The methodology used is qualitative research with data collection techniques in the form of in-depth interviews, observations, and document analysis. The results of the study indicate that the process of implementing a Learning Management System (LMS) with interactive features has proven to be an effective solution in supporting flexible, collaborative, and more participatory learning. Features such as discussion forums, virtual classes, online assignments, and student progress analysis provide various benefits for the teaching and learning process, both for students and teachers. Recommendations for LMS with interactive features not only optimize online learning but also enrich the overall learning experience, making it an important platform in the world of modern education. Recommendations for optimizing interactive learning are to provide training to lecturers and students in using LMS, provide adequate internet access, and combine online learning with face-to-face learning that supports social interaction. Continued support from institutions in terms of infrastructure and training will be critical to ensure a more mature and comprehensive implementation in the future.